An investigation of the role of news values in the selection of news sources in a contemporary third world newspaper: a case study of the Daily Nation newspaper - Kisuke, Connie Syomiti (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2005)
News in our contemporary newspapers has come to be associated more and more with what the elites do and say. Both their deeds and misdeeds are treated as newsworthy events and in the process they become newsmakers, both actors and sources of news. Even when they are not directly involved in news events they are sought out by journalists to validate those events and to interpret the social reality to the readers as news sources. This study is about the selection of news sources in the Daily Nation, a contemporary, independent newspaper based in Nairobi, Kenya. In this study, I set out to unravel the complex processes that underlie newsmaking and source selection. This study is informed by the theory of news values and the paradigm of the role of media in democracy. Based on qualitative interviews, observations and content analysis of the front-page stories, it investigates the process of news and source selection in front-page stories. Through these approaches, I established that news values are significant criteria that inform journalists in both the selection of front-page news stories and the sources of these stories. I also established that social values of the society in which this newspaper operates are heavily embedded in the news. For example, the journalists preferred male politicians as sources of news in the front-page stories to women, and the elites to ordinary people, and this reflected on the social structures and cultural norms that are prevalent in this society. This study, further, established that the news values of this newspaper share commonly with the Western news media in terms of journalistic conventions and ways of interpreting the social reality in the news. Ideally, the newspaper embraces the principles of democracy in news reporting, but in practice it does not satisfactorily adhere to the full requirements of its democratic role in terms of source selection. The democratic principles in news reporting require, among other things, that the newspaper should allow a diversity of views in the news, representing various groups that are found in real society including the elites, non-elites, women, ordinary people and minorities. In the case of the Daily Nation, a tiny group of elite male professional politicians made up the largest majority of its front-page news sources.
Keywords: Daily Nation (Nairobi, Kenya); Government and the press -- Africa; Reporters and reporting; Mass media -- Political aspects -- Africa; Newspapers -- Africa; Journalism -- Social aspects